(untitled) (Pulse, 2026)
Background: Peritoneal inflammatory nodules are rare, non-neoplastic lesions that can be associated with endometrioid carcinoma of the uterus. Grossly, these lesions may closely resemble peritoneal carcinomatosis, creating significant intra-operative diagnostic dilemmas and risking erroneous upstaging. Case Presentation: We report a case of a 65-year-old postmenopausal woman with endometrioid carcinoma in whom widespread multiple “seedling-like” pelvic peritoneal deposits were observed intra-operatively and were suspicious for advanced disease. Total abdominal hysterectomy with bilateral salpingo-oophorectomy, pelvic lymphadenectomy, and pelvic peritonectomy were performed. Comprehensive Histopathological examination confirmed endometrioid carcinoma with <50% myometrial invasion and negative pelvic lymph nodes. Peritoneal and omental samples showed inflammatory changes without evidence of tumour deposit, confirming a final pathological stage of pT1aN0. The patient was managed according to early-stage disease and received adjuvant vaginal brachytherapy alone. Conclusion: Recognizing this benign condition prevents incorrect staging and unnecessary treatment. This case highlights the importance of this distinction. Pulse Volume 17, Issue 2 2025; 25-29